The Concept of Health and the Process of Generalization - Torres, Juan Manuel (Revista de Humanidades de Valparaíso, 2014)
Health means today something more than the absence of illness or suffering of disability, as the pioneer theories of health had assumed. To be healthy also involves not having genetic mutations that indicate inexorably premature dead or serious disabilities. Genetic tests, whose amount and use grow day by day, have open these predictive possibilities for medicine and, at the same time, influenced for a more strict notion of health. The pathology known as ‘Huntington’s Chorea’ is an example of this kind of situations. Because of the concept of health has deep economical, ethical and legal implications –among others-, it is evident that its modification will influence on society, something that now is occurring in some medical practices. The transformation process of the notions of health and unhealth supports –albeit in part- the sociological thesis that affirm that west society is undergoing a geneticization process.